2021
DOI: 10.3390/cancers13092276
|View full text |Cite
|
Sign up to set email alerts
|

Role of IQGAP1 in Papillomavirus-Associated Head and Neck Tumorigenesis

Abstract: Approximately 25% of head and neck squamous cell carcinomas (HNSCC) are associated with human papillomavirus (HPV) infection. In these cancers as well as in HPV-associated anogenital cancers, PI3K signaling is highly activated. We previously showed that IQ motif-containing GTPase activating protein 1 (IQGAP1), a PI3K pathway scaffolding protein, is overexpressed in and contributes to HNSCC and that blocking IQGAP1-mediated PI3K signaling reduces HPV-positive HNSCC cell survival and migration. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 72 publications
6
21
0
Order By: Relevance
“…MmuPV1 can infect the mouse epithelium and cause cancers to arise in different anatomical sites in mice, including the head and neck region [104][105][106][107], which provides opportunities to study the pathogenesis of papillomavirus (PV) in a genetically manipulatable and trackable model organism. MmuPV1 infection upregulates PI3K signaling in keratinocytes [103], which is in line with a previous report showing that HPV16 pseudovirus infection upregulates PI3K signaling in vitro [108]. We also showed that this MmuPV1-induced PI3K signaling was greatly diminished in keratinocytes knocked out for IQGAP1 [103].…”
Section: Iqgap1 In Head and Neck Cancersupporting
confidence: 92%
See 4 more Smart Citations
“…MmuPV1 can infect the mouse epithelium and cause cancers to arise in different anatomical sites in mice, including the head and neck region [104][105][106][107], which provides opportunities to study the pathogenesis of papillomavirus (PV) in a genetically manipulatable and trackable model organism. MmuPV1 infection upregulates PI3K signaling in keratinocytes [103], which is in line with a previous report showing that HPV16 pseudovirus infection upregulates PI3K signaling in vitro [108]. We also showed that this MmuPV1-induced PI3K signaling was greatly diminished in keratinocytes knocked out for IQGAP1 [103].…”
Section: Iqgap1 In Head and Neck Cancersupporting
confidence: 92%
“…Given the importance of PI3K signaling in HPV-positive HNSCC and the role of IQGAP1 in scaffolding PI3K signaling [48], we hypothesized that IQGAP1 also plays a role in HPV-positive HNSCC. We found that HPV16 E6 upregulated PI3K signaling in normal oral keratinocytes, while E7 only mildly impacted its signaling [103]. Loss of IQGAP1 significantly reduced the PI3K signaling levels in both E6-and E7-expressing keratinocytes [103], indicating HPV16 oncoproteins regulate PI3K signaling in an IQGAP1dependent manner.…”
Section: Iqgap1 In Head and Neck Cancermentioning
confidence: 78%
See 3 more Smart Citations